Utilization of Indonesia’ Natural Resources as Raw Materials in Pharmaceutical Industries for the Treatment of Degenerative Diseases - AGI MEISARANI; Rano K. Sinuraya (Fakultas Farmasi, Universitas Padjadjaran, 2018)
In Indonesia, health problems such as treatment of degenerative diseases are still not be handled properly. The common degenerative diseases in Indonesia are diabetes mellitus and hypertension. Generating qualified medicines with lower cost for degenerative disease are still be a major problem because Indonesia has not been independent in pharmaceutical raw materials. Raw materials are important part in the production process of pharmaceutical preparations. Indonesia obtained raw materials by importing from various countries. By looking at the various potentials of natural resources that can be used as a source of raw material in pharmaceutical industries, both active pharmaceutical ingredients (API) and excipients, Indonesia will be able to independently produce the pharmaceutical raw materials. To achieve independency of pharmaceutical raw materials, the appropriate processing methods to produce quality raw materials is needed. Based on this issue, a review of various studies was performed including the processing of API and pharmaceutical excipients raw materials of plant and animal body parts. “Kayu Manis” (Cinnamomum burmanii) and “Brotowali” (Tinospora cripa L.) which can be utilized as raw material pharmaceutical ingredient for the treatment of diabetes mellitus and “Mengkudu